2015
DOI: 10.1016/s1701-2163(16)30050-0
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Association Between Psychiatric Disturbances and Endometriosis

Abstract: Objective: An association between endometriosis and psychiatric disturbances has been identified by some researchers. The purpose of this systematic review was to consolidate existing empirical findings to clarify the association between endometriosis and psychiatric conditions .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
100
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(114 citation statements)
references
References 57 publications
8
100
1
5
Order By: Relevance
“…They found that 86.5% presented depressive symptoms and 87.5% presented anxiety and, most important, that psychiatric symptoms were not associated with endometriosis stage 33. In this study, age correlated positively with depressive symptoms, while there was no association between age and anxiety symptoms 25,33. Nevertheless, other authors found that only 29% of endometriotic women showed moderate to severe anxiety symptoms, while depression was present in 14.5% 21…”
Section: Anxiety and Depressive Symptoms In Women With Endometriosiscontrasting
confidence: 55%
See 1 more Smart Citation
“…They found that 86.5% presented depressive symptoms and 87.5% presented anxiety and, most important, that psychiatric symptoms were not associated with endometriosis stage 33. In this study, age correlated positively with depressive symptoms, while there was no association between age and anxiety symptoms 25,33. Nevertheless, other authors found that only 29% of endometriotic women showed moderate to severe anxiety symptoms, while depression was present in 14.5% 21…”
Section: Anxiety and Depressive Symptoms In Women With Endometriosiscontrasting
confidence: 55%
“…Pope et al25 underlined that endometriosis is related to a wide range of psychiatric symptoms, especially depression, anxiety, psychosocial stress and a poor quality of life. According to recent literature,21,23,2531 depression and anxiety are the most common disorders associated with endometriosis. In this context, Low et al32 investigated the possibility of a specific psychological profile associated with endometriosis.…”
Section: Anxiety and Depressive Symptoms In Women With Endometriosismentioning
confidence: 99%
“…La ansiedad y depresión son los trastornos que más presentan comorbilidad en la endometriosis, y tienden a co-ocurrir de manera conjunta (7,21,22), encontrándose niveles altos de ansiedad rasgo en las mujeres con esta enfermedad. (4).…”
Section: Respuesta Emocional Y Desordenes Psiquiátricosunclassified
“…Las mujeres con endometriosis presentan mayores niveles de psicoticismo e introversión que otras condiciones ginecológicas (24 en 7) y presentan una asociación con trastorno bipolar (7). Por otro lado, no presentan diferenciación en índices de trastorno obsesivo compulsivo, ideación paranoide y rabia (21).…”
Section: Respuesta Emocional Y Desordenes Psiquiátricosunclassified
“…Individuals with chronic pain are known to be at increased risk of psychiatric disorders, particularly those involving low mood and anxiety [1][2][3] and Posttraumatic Stress Disorder (PTSD) [4,5]. Evidence shows that chronic pain sufferers with comorbid anxiety, depression, and PTSD present with greater levels of pain-related impairment, respond less well to pain focused treatment, and incur greater health costs [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%